2008
DOI: 10.1007/s11274-008-9919-8
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effects of some laboratory-derived genetic mutations on biofilm formation by Listeria monocytogenes

Abstract: Biofilms formed by the human pathogen Listeria monocytogenes in food-processing environments can be a potential source of contamination. In this study, we investigated the ability of L. monocytogenes wild type and its laboratory-derived isogenic mutants in cwhA, prfA, agrA, flaA, degU, ami and sigB to adhere to and form biofilms on abiotic surfaces. The results suggest that inactivation of the two component regulatory system degU completely abolished biofilm formation, while inactivation of the flagellar gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 18 publications
2
23
0
1
Order By: Relevance
“…In another study, Zhou et al (48) successfully identified 47 proteins that were either up-or down-regulated in bacteria in the biofdm state. This coordinated gene expression includes the production of regulators associated with the response to stress, the expression of motility genes, the production of biofilm-associated proteins and proteins related to cell-cell communication pathways, and polysac charide biosynthesis (15,16,19,21,37,39). In contrast, a rich culture medium such as TSB supports bacterial growth and biofilm formation but contains biological macromol ecules likely to produce conditioning films, as the present study clearly shows with TSB-coated PS.…”
Section: Discussionsupporting
confidence: 49%
“…In another study, Zhou et al (48) successfully identified 47 proteins that were either up-or down-regulated in bacteria in the biofdm state. This coordinated gene expression includes the production of regulators associated with the response to stress, the expression of motility genes, the production of biofilm-associated proteins and proteins related to cell-cell communication pathways, and polysac charide biosynthesis (15,16,19,21,37,39). In contrast, a rich culture medium such as TSB supports bacterial growth and biofilm formation but contains biological macromol ecules likely to produce conditioning films, as the present study clearly shows with TSB-coated PS.…”
Section: Discussionsupporting
confidence: 49%
“…Although the characteristic tumbling motility of L. monocytogenes was observed in all of our 27 isolates, the flaA gene was not detected from four of these motile isolates, stipulating that there are alternative mechanisms controlling the flagella and the secretion of other flagella-related proteins involved in the synthesis of the L. monocytogenes flagellum required for its motility and the secretion of supplementary flagellar-related proteins [60]. Attachment and formation of biofilm allows the colonization of surfaces, including food processing environments [61]. The presence of LIPI-1 genes, hly and prf A, is required for efficient biofilm formation by L. monocytogenes [62]; however, the current study was unable to detect a correlation between the strength of attachment and biofilm formation and detection of the hlyA gene or amino acid substitutions in prf A.…”
Section: Discussionmentioning
confidence: 75%
“…Various studies have demonstrated that specific genes in L. monocytogenes are required for different phases of biofilm formation. In L. monocytogenes, agr (accessory gene regulator) and ami (autolysin-adhesion gene) mutants were shown to be defective in the initial attachment to a surface (57,84,91). Also, genomic studies exploring gene expression during growth of L. monocytogenes on a surface demonstrated that the DegU orphan response regulator was important for biofilm formation (43,57).…”
mentioning
confidence: 99%